FLOWERS FOR ELDERLY PEOPLE IN UKRAINE. SAMBUCUS NIGRA’S FLOWERS (FLOWERS OF ELDERBERRY) USING FOR PREVENTION AND TREATMENT OF THE BURN-OUT SYNDROME AND NON-ALCOHOL FATTY LIVER’S DISEASE - Гайова, І. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
In the article, on the base of modern literature, the author has offered to use decoction of flowers of elderberry for prevention and for use in the complex treatment of the burn-out syndrome and non-alcohol fatty liver’s disease. Flowers of elderberry are rich for choline, the source of neurotransmitter acetylcholine, stimulating the congenital functions, prevent and treat the burn-out syndrome. The cerebral activity is optimized due to the systemic effects of the aminoacids betain and ademethionine (SAMe). Considerable hepatoprotective effect let to offer flowers of elderberry’s decoction for prevention and complex medical treatment of non-alcohol fatty liver’s disease.